Ecolinguistic Approaches in Development of English Teaching Materials for English for Business - Krismayani, Ni Wayan; Suastra, I Made; Suparwa, I Nyoman (e-Journal of Linguistics; Vol 15 No 1 (2021): ejl-JanuaryDO - 10.24843/e-jl.2021.v15.i01.p03, 2021)
This study aims at finding an English learning model using an ecolinguistic approach in the preparation of syllabus and teaching materials. Qualitative descriptive methods are applied and natural phenomena are used to develop syllabus. This phenomenon focuses on learning and teaching strategies that are applied. Data obtained through tests, questionnaires and direct observation for needs analysis. The syllabus was developed based on the results of material analysis and needs.The ecological approach in education has the aim to preserve nature and its contents by building an environmentally friendly character. From this rationale, the ecological approach in language education has a number of characters that are used to find new ways to be applied to language learning. The result of the study shows that teaching materials have met the characteristics of the ecolinguistic approach, namely: relations, context, patterns / systems, emergence, quality, value, critical, variability, diversity, and activity. These characteristics are used as a theoretical basis for this research.